Development of a Low-Cost and Portable Device for Monitoring Heart Rate, Blood Oxygen Saturation, and Body Temperature in Infants Incubator - Nur Astrif, Citra; Triwiyanto, Triwiyanto; Abdullayev, Vugar (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
The risk of newborn infant mortality is commonly associated with hypothermia. Hypothermia is a health disorder and a leading cause of death in newborns. caused by an imbalance in the baby's body temperature. Hypothermia is caused by a decrease in body temperature, which can result from various conditions, including high oxygen requirements and a decrease in room temperature, among other factors. Hypothermia occurs due to a decrease in body temperature resulting from various conditions. especially high oxygen requirements and a decrease in room temperature. The purpose of this study is to monitor the health status of newborns. Monitoring the body temperature and oxygen saturation levels in newborns can help detect abnormalities in infants at an early stage. This research is expected to assist patients using a baby cube in providing care for newborns with hypothermia symptoms. The Baby Cube utilizes the DS18B20 sensor for temperature measurement and the MAX3102 sensor for heart rate and oxygen saturation. The data is then processed using the ESP32 microcontroller. and the results are displayed on an LCD screen. The comparative tools used in this study are the standard thermometer and pulse oximeter. The results of this research indicate that the smallest measurement error value is found in the SpO2 measurement of data collection 10. which is 0.1%. The largest measurement error value is found in the SpO2 measurement of data collection 2. which is 5.6% based on the obtained data. However. the measurement results are still within the tolerance limit of ±10%.